Electron-impact excitation of singly charged metal ions - Sharma, Lalita; Surzhykov, Andrey; Srivastava, Rajesh; Fritzsche, Stephan (Physical review. A, Atomic, molecular, and optical physics, 2011)
Fully relativistic distorted-wave theory has been applied to study the electron-impact excitation of the ns1/2-np1/2 and ns1/2-np3/2 resonance transitions of singly charged metal ions with one valence electron, viz., Mg+ (n=3), Ca+ (n=4), Zn+ (n=4), Cd+ (n=5), and Ba+ (n=6). Calculations are performed in the range of incident electron energies up to 300 eV for differential and integrated cross sections as well as for the linear polarization of the photon emissions following the decay of excited np3/2 states. Results are compared with the available experimental data and previous nonrelativistic theoretical calculations. Moreover, analytic fits to our integrated cross sections are provided for potential applications in modeling plasma sources and environments.
Gesehen am 30.11.2022